Pengaruh Edukasi Kesehatan Terhadap Perilaku Pencegahan Dbd Pada Masyarakat Di Wilayah Pesisir - Mukhlis, Mukhlis (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains one of the most serious public health problems in Indonesia, particularly in coastal areas where environmental conditions are favorable for the breeding of Aedes aegypti mosquitoes. Low levels of community awareness and preventive behavior often contribute to the persistence of dengue cases. Health education is one of the community nursing interventions that can improve knowledge, attitudes, and preventive practices. Objective: This study aimed to determine the effect of health education on dengue fever prevention behavior among communities living in coastal areas. Methods: This research used a pre-experimental design with a one group pretest–posttest approach. The sample consisted of 40 respondents selected through purposive sampling. Health education about dengue prevention was delivered through lectures and leaflets for 60 minutes. Data were collected using a validated questionnaire covering knowledge, attitudes, and practices related to dengue prevention. Data analysis was performed using a paired sample t-test to compare the mean scores before and after the intervention. Results: The findings showed a significant improvement in dengue prevention behavior after health education. The mean score increased from 65.7 before the intervention to 82.4 after the intervention. Statistical analysis yielded a p-value = 0.000 (p < 0.05), indicating a significant effect of health education on dengue prevention behavior. The largest improvement occurred in the knowledge aspect, followed by attitudes and practices. Conclusion: Health education effectively improves dengue fever prevention behavior among coastal communities. It enhances community knowledge, shapes positive attitudes, and encourages preventive actions such as draining water containers, closing water storage, and using mosquito repellents. Community nurses are encouraged to conduct regular and continuous health education programs to reduce dengue incidence in coastal regions.